Status” of family institution in the contemporary society, and family and marriage values of the youth - I V Trotsuk; A D Paramonova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
In recent years, in the scientific community and the media there are ongoing debates on how radically the structure, functions and role of the family change in the contemporary society. The positions are conflicting, and even irreconcilable - from quite idealistic family perception in the social-constructivist sense (as a result of agreement of people without any traditional links - biological or legal), which states the eternal nature of the family, as long as there are people and some forms of sociality, to extremely alarmist warnings about the crisis of the family in the present and its disappearance in the not too distant future due to the loss of its functions as a basic social institution. The authors acknowledge both types of arguments, but introduce a clarification: the most pessimistic estimates and forecasts of the future of the family are concentrated on the theoretical level of the studies of the family as primarily a social institution, while at the empirical level, when people answer relevant questions about their own family, the current social realities do not look too pessimistic and prove both ideas - of the transformation of family values and of the preservation of many traditional patterns. Such a conventional differentiation of theoretical and empirical levels in terms of emphases in the sociological study of the family is presented in the article: first, the authors refer to the main trajectories of conceptual searches on family issues in historical and evaluative approaches; then present the results of the surveys among students of universities in the capitals of Russia, Kazakhstan and the Czech Republic. The data confirms, on the one hand, the reproduction in the youth worldview of quite traditional ideas about the proper and important in a person’s life (family is an absolute priority); on the other hand, the ambivalence of Russian youth consciousness, which combines quite easily patriarchal and self-centered Western values.